Building an Artificial Cardiac Microenvironment: A Focus on the Extracellular Matrix - Pagliarosi, Olivia; Picchio, Vittorio; Chimenti, Isotta; Messina, Elisa; Gaetani, Roberto (Frontiers in Cell and Developmental Biology, 2020)
The increased knowledge in cell signals and stem cell differentiation, together with the development of new technologies such as 3D bioprinting and micropatterning, has made the generation of artificial tissues more feasible for in vitro studies and in vivo applications. In the human body, the fate, function, and survival of cells are determined by the microenvironment, a rich and complex network composed of extracellular matrix (ECM), different cell types, and soluble factors. They all interconnect and communicate, receiving and sending signals, modulating and responding to cues. In the cardiovascular field, the culture of stem cells in vitro and their differentiation into cardiac phenotypes is well established, although differentiated cardiomyocytes often lack the functional maturation and structural organization typical of the adult myocardium. The recreation of an artificial microenvironment as similar as possible to the native tissue, though, has been shown to partly overcome these limitations, and can be obtained through the proper combination of ECM molecules, different cell types, retained growth factors, as well as appropriate mechanical and geometrical stimuli. This review will focus on the role of the ECM in the regulation of cardiac differentiation, will provide new insights on the role of supporting cells in the generation of 3D artificial tissues, and will also present a selection of the latest approaches to recreate the cardiac microenvironment in vitro.